2004
DOI: 10.3168/jds.s0022-0302(04)73530-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alfalfa Particle Size and Specific Gravity on Chewing Activity, Digestibility, and Performance of Holstein Dairy Cows

Abstract: Two experiments were carried out to test the effects of alfalfa particle size and functional specific gravity (FSG) on chewing activity, digestibility, rumen kinetics, and production of lactating dairy cows fed corn silage based rations. In experiment 1, water-holding capacity (WHC), insoluble dry matter, hydration rate, and FSG changes were determined in alfalfa hay (varying in particle size) and corn silage. Reduction of particle size increased bulk density, FSG, and the rate of hydration, and decreased WHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
38
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 23 publications
13
38
2
2
Order By: Relevance
“…Krause et al (2002) reported that mean ruminal pH was positively correlated with the time spent on ruminating and chewing. Our results concerning forage PS are in agreement with those of other authors (Krause et al, 2002;Teimouri Yansari et al, 2004), confirming that forage PS plays a major role in maintaining opti- Gain-to-feed ratio was calculated by dividing ADG (g) by average daily DMI.…”
Section: Rumen Fermentation Parameters and Blood Metabolitessupporting
confidence: 94%
“…Krause et al (2002) reported that mean ruminal pH was positively correlated with the time spent on ruminating and chewing. Our results concerning forage PS are in agreement with those of other authors (Krause et al, 2002;Teimouri Yansari et al, 2004), confirming that forage PS plays a major role in maintaining opti- Gain-to-feed ratio was calculated by dividing ADG (g) by average daily DMI.…”
Section: Rumen Fermentation Parameters and Blood Metabolitessupporting
confidence: 94%
“…This finding was confirmed by Mansfield et al [31], but was in contrast to the findings of Valk et al [22]. In contrast to the current experiment, a lower intake of CP, lower NH 3 -N concentrations in the rumen, and lower CP degradability for cows fed on BP was observed, compared with that in cows fed on corn [20] or barley [33]. The consumption of carbohydrates such as NDSC that are more extensively fermented in the rumen may improve the utilization of the NPN through the stimulation of microbial protein synthesis.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, compared with barley, BP created more favorable conditions for microbial utilization of other carbohydrates in the rumen, at least in part due to the neutral pH. Decreasing daily mean ruminal pH, which was associated with an increase in ruminal outflow rate of digesta, resulted in a decrease in ruminal NDF digestibility and total tract digestibility [2,8,9,33]. Zebeli et al [9] showed a decrease in total tract NDF digestibility by increasing the outflow rate of particulate digesta, which was associated with a decrease in ruminal mat consistency.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, Kowsar et al (2008) reported an increased in DM digestibility when fine particle of alfalfa hay was added to corn silagebased diet. The improvement in milk production with decreasing FPS in our study is interesting because previous research studies (Kononoff and Heinrichs, 2003a;Teimouri Yansari et al, 2004;Alamouti et al, 2009) and review articles , as well as meta-analyses (Zebeli et al, 2006;Tafaj et al, 2007), uniformly indicated no significant effect of FPS on milk production, although DMI was mostly improved in all these studies. In the current meta-analysis, we used a large number of experimental findings and a more precise statistical approach, which was able to detect even marginal effects of FPS.…”
Section: Figurementioning
confidence: 55%